Strategi Pengembangan Ekowisata Pantai Tirta Samudra Jepara - Gemilang Mohammad Sakti; Lilik Kartika Sari (Jurnal Ilmu Kelautan Lesser Sunda, 2022)
Tirta Samudra Beach is a beach that is quite famous and has become a mainstay of Jepara Regency so that it becomes a fairly popular tourist destination, not only for the people of Jepara, but also most of the population of Central Java and even outside the province. Currently, tourism activities on Tirta Samudra Beach are very limited to just recreation, enjoying the panoramic beauty of the coast, and swimming activities. While there is still a lot of physical potential in the form of a coastal environment that has not been fully utilized, such as water sports tourism, vacant land, and so on. Its natural beauty is in great demand by many people, therefore it can cause environmental damage because it is often visited by visitors. Therefore, it is necessary to analyze and study the tourism industry strategy to find out what is needed to keep attracting visitors and minimize environmental damage. The purpose of this study is to analyze the potential and to anticipate the development strategy of tourism objects in Tirta Samudra Beach. The method used is a field survey with data collection using observations, questionnaires, and documentation to tourists and local managers.